Evolution of Earth and its climate : birth, life and death of Earth - Sorokhtin, O. G.; Chilingarian, G. V.; Sorokhtin, N. O. (Developments in earth & environmental sciences, 2011)
The book reviews the current physical theory of Earth's global evolution, its origin, structure and composition, the process ofEarth's core formation, Earth's energy, and the nature of its tectonomagnetic activity. The book also deals with the origin of the Moon and its influence on our planet's evolution. Based on the integral positions of this theory, the book analyzes the issues of the origin of the hydrosphere and atmosphere, and the conception and evolution of life on Earth. The monograph also reviews the adiabatic theory of the greenhouse effect developed by the authors, and the ef.